Do Chinese Teachers Perform Emotional Labor Equally? Multi-Group Comparisons Across Genders, Grade Levels and Regions - Huang, Shenghua; Yin, Hongbiao; Han, Jiwei (Frontiers in Psychology, 2019)
The emotional aspects of teaching are important and teachers’ emotional labour, or, how teachers manage emotions at school, has been attracting more and more attention recently. Using multi-group structural equation modelling, this study investigated the measurement invariance of, and the relationships between, teachers’ emotional labour strategies and teaching satisfaction. Participants included teachers from primary and secondary schools in Hong Kong and mainland China. Three sets of group comparisons have been made between female and male teachers, between primary and secondary school teachers, and between teachers in Hong Kong and mainland China. The multi-group invariance tests showed no significant subgroup differences in the measurement and structural models. Thus, there was no difference of ‘kind’. However, some differences of ‘degree’ were observed across genders, grade levels and regions. These differences in the relationship between surface/deep acting and teaching satisfaction can be attributed to the possible influence of some cognitive factors and socio-cultural contexts. With due methodological rigor, the results of this study provide deeper understanding of teachers’ emotional labour and its relationship with teaching satisfaction.